Children’s play and subjectivity: reflections upon the little house play - Aline Sommerhalder; Fernando Donizete Alves (Educação: Teoria e Prática, 2011)
In a dialogue with psychoanalysis as its theoretical foundation, the paper aims to address constitutive aspects of children’s play in a school toy library environment. For doing this, the study presents a reflection on the results of six sessions of observation of the ”little house play” among kindergarten children. The observation of this ludic activity was completed by the record in a field diary containing the actions and speech of the thirteen children participating in the study. It shows that children’s play constitutes a subjective space and it is a preferred vehicle for the symbolic fulfillment of desires and fantasies, the reality transformation, and the creation of new knowledge. Therefore, the importance of appreciating the toy library at school isstressed as a way of recalling and executing children’s play in kindergarten educationand the study highlights the value of this ludic play for the learning and development of children in this education level.